Obatoclax potentiates the cytotoxic effect of cytarabine on acute myeloid leukemia cells by enhancing DNA damage. Issue 2 (2nd October 2014) - Xie, Chengzhi; Edwards, Holly; Caldwell, J. Timothy; Wang, Guan; Taub, Jeffrey W.; Ge, Yubin
Abstract : Resistance to cytarabine and anthracycline‐based chemotherapy is a major cause of treatment failure for acute myeloid leukemia (AML) patients. Overexpression of Bcl‐2, Bcl‐xL, and/or Mcl‐1 has been associated with chemoresistance in AML cell lines and with poor clinical outcome of AML patients. Thus, inhibitors of anti‐apoptotic Bcl‐2 family proteins could be novel therapeutic agents. In this study, we investigated how clinically achievable concentrations of obatoclax, a pan‐Bcl‐2 inhibitor, potentiate the antileukemic activity of cytarabine in AML cells. MTT assays in AML cell lines and diagnostic blasts, as well as flow cytometry analyses in AML cell lines revealed synergistic antileukemic activity between cytarabine and obatoclax. Bax activation was detected in the combined, but not the individual, drug treatments. This was accompanied by significantly increased loss of mitochondrial membrane potential. Most importantly, in AML cells treated with the combination, enhanced early induction of DNA double‐strand breaks (DSBs) preceded a decrease of Mcl‐1 levels, nuclear translocation of Bcl‐2, Bcl‐xL, and Mcl‐1, and apoptosis. These results indicate that obatoclax enhances cytarabine‐induced apoptosis by enhancing DNA DSBs. This novel mechanism provides compelling evidence for the clinical use of BH3 mimetics in combination with DNA‐damaging agents in AML and possibly a broader range of malignancies. Highlights: Obatoclax enhances cytarabine‐induced DNA damage prior to induction of apoptosis. Combined obatoclax and cytarabine treatment decreases Mcl‐1 levels. Cytarabine plus obatoclax induces nuclear localization of Bcl‐2, Bcl‐xL & Mcl‐1. Bcl‐2, Bcl‐xL, and Mcl‐1 modulate cytarabine‐induced DNA damage.